What is it that matters most in the practice of nursing children? - M Coetzee (AOSIS, 2000)
This article discusses the results of a workshop designed as an action research cycle to ascertain what matters most in the practice of nursing children in South Africa today. The workshop was convened at the University of Cape Town (UCT), in order to guide and direct the newly established post- basic, children's nursing pathway in the Bachelor of Nursing for Registered nurses [BN(RN)] programme. The participants were eight experienced paediatric nurses, currently practising in a variety of settings in the Western Cape. The results show that the participants move from their original task- and procedure - based perspective to a more processive one in which the focus of the learning is relational, emphasising the family and culture of the child.